2023
DOI: 10.3390/ma16093298
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of the Porous Structure of Gyroid and Voronoi Hip Implants: A Finite Element Analysis Using an Experimentally Validated Model

Abstract: Total hip arthroplasty (THA) is most likely one of the most successful surgical procedures in medicine. It is estimated that three in four patients live beyond the first post-operative year, so appropriate surgery is needed to alleviate an otherwise long-standing suboptimal functional level. However, research has shown that during a complete THA procedure, a solid hip implant inserted in the femur can damage the main arterial supply of the cortex and damage the medullary space, leading to cortical bone resorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 56 publications
(84 reference statements)
0
27
0
Order By: Relevance
“…The authors pointed out that texture features have been important in most of the selected studies, and they identified the need for well-designed prospective studies to assess the value of radiomics in classifying renal neoplasia. CT is adequate for the analysis of the fine structure of hard and soft materials [38][39][40], being an excellent method for the extraction of fine radiomics information. These features can be used with in silico approaches that are important in simulating conditions and data that are not readily available in research and clinical practice, reducing experimental time and associated costs [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The authors pointed out that texture features have been important in most of the selected studies, and they identified the need for well-designed prospective studies to assess the value of radiomics in classifying renal neoplasia. CT is adequate for the analysis of the fine structure of hard and soft materials [38][39][40], being an excellent method for the extraction of fine radiomics information. These features can be used with in silico approaches that are important in simulating conditions and data that are not readily available in research and clinical practice, reducing experimental time and associated costs [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging is in continuous technological progress; new possibilities, such as artificial intelligence, are yet to be explored in nerve imaging, and further studies are needed [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This work used Star CCM+ software to In order not to be impacted by varying mesh sizes, a convergence analysis [41] was conducted to guarantee the quality of the particle collection model. Since the nodule discussed in this work is a coarse particle, the trimmed mesh and the advancing layer mesh are used to generate the meshes which have been shown to be more suitable for the fluid-structure interaction of coarse particles [42]. This work used Star CCM+ software to generate four mesh densities ranging from 3 mm to 2.4 mm at the suction velocity of 1.8 m/s, and compared the calculation of the vertical forces in four models.…”
Section: Physical Modeling and Meshingmentioning
confidence: 99%